2020
DOI: 10.1101/2020.03.26.20041491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of training general practitioners in the ABC versus 5As method of delivering brief stop-smoking advice: a pragmatic, two-arm cluster randomised controlled trial

Abstract: OBJECTIVE To assess the effectiveness of a 3.5h-training for general practitioners (GPs) in two different methods (ABC, 5As) of giving brief stop-smoking advice during routine consultations. DESIGN Pragmatic two-arm cluster randomised controlled trial with pre-post-design for the primary outcome and cluster randomisation for secondary outcomes. SETTING General practices, North Rhine-Westphalia (German federal state), recruited 2017-2019. PARTICIPANTS Practices were randomised (1:1) to an ABC or 5As traini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, HPs should be trained to further encourage, and effectively support, smokers with MHCs in translating their motivation to quit into successful abstinence. Training in the effective treatment of tobacco addiction is not standard in the medical education in Germany, although such training can substantially increase HPs’ provision of advice on smoking cessation and of recommendation on the use of evidence-based cessation treatments [55]. For smokers with MHC who are motivated to quit but have difficulties to achieve abstinence, medical counselling and, in particular, the recommendation of evidence-based behavioural support and cessation medication are of particular importance [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HPs should be trained to further encourage, and effectively support, smokers with MHCs in translating their motivation to quit into successful abstinence. Training in the effective treatment of tobacco addiction is not standard in the medical education in Germany, although such training can substantially increase HPs’ provision of advice on smoking cessation and of recommendation on the use of evidence-based cessation treatments [55]. For smokers with MHC who are motivated to quit but have difficulties to achieve abstinence, medical counselling and, in particular, the recommendation of evidence-based behavioural support and cessation medication are of particular importance [21].…”
Section: Discussionmentioning
confidence: 99%
“…As described in WP1, we calculate with an estimate of 20% of patients who report the receipt of brief PA advice during their GP visit without the GP having been trained. Another study showed that a brief singlesession GP training can increase patient-reported rates of GP-delivered stop-smoking advice by 20%points on average (52). Training GPs to deliver PA advice might be more challenging, e.g., because PA recommendations are more complex than simple advice on smoking cessation methods.…”
Section: <<<<<<<<<<<<<<<<<<<<<<<<< Place Here Figure 2 >>>>>>>>>>>>>>...mentioning
confidence: 99%
“…All patients will be included in an intention-to-treat analysis. Based on experiences from another cRCT (52), missing data on the primary outcome is assumed to be minimal as data will be collected through face-to-face interviews. However, multiple imputation will be applied to impute missing data if needed.…”
Section: Analyses Wp6mentioning
confidence: 99%
“…It is critical to address a patient's cigarette smoking at each clinic visit. Providers can use the ABC pathway for smoking cessation: Ask about and document every person's smoking status, give Brief advice to stop smoking to each patient who smokes, strongly encourage every person who smokes to use Cessation support (offer to help them access it; refer to, or provide, cessation support to everyone who accepts your offer) 7…”
Section: Risk Factorsmentioning
confidence: 99%